Analysis of The Influence of Marketing Strategies and Excellent Service on Increasing Sales Volume - Sari, Nila; Septika, Baiq Herdina; Supratman, Supratman (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Trade enterprises (UD) in Indonesia that are able to survive and thrive are usually driven by strong networks, healthy organizations, and effective competitive strategies. Along with industry development and increasingly fierce competition, companies are required to continuously adapt to changing market needs and preferences. UD Bangunan Tiara, as one of the major players in the building materials industry in East Lombok, faces challenges in increasing its sales volume. This study aims to analyze the effect of marketing strategies and excellent service on sales volume at UD Tiara, East Lombok Regency. The research method used is quantitative with multiple linear regression analysis techniques. The population in this study were all UD Tiara customers, with a sample of 60 respondents. The results showed that the F-count value of 428.603 was greater than the F-table of 3.150, which indicated that the variables of marketing strategy and excellent service simultaneously had a significant positive effect on sales volume. These findings provide insight for UD Tiara's management to continue strengthening marketing strategies and service quality to increase sales in the future. Keywords: Marketing Strategy, Excellent Service, Sales Volume